RECQ5: A Mysterious Helicase at the Interface of DNA Replication and Transcription - Andrs, Martin; Hasanova, Zdenka; Oravetzova, Anna; Dobrovolna, Jana; Janscak, Pavel (Genes, 2020)
RECQ5 belongs to the RecQ family of DNA helicases. It is conserved from Drosophila to humans and its deficiency results in genomic instability and cancer susceptibility in mice. Human RECQ5 is known for its ability to regulate homologous recombination by disrupting RAD51 nucleoprotein filaments. It also binds to RNA polymerase II (RNAPII) and negatively regulates transcript elongation by RNAPII. Here, we summarize recent studies implicating RECQ5 in the prevention and resolution of transcription-replication conflicts, a major intrinsic source of genomic instability during cancer development.
Keywords: RecQ Helicases; nestabilita genomu; Transcription, Genetic; replication stress; transcription-replication conflicts; DNA repair; RECQ5; Genomic Instability; genetická transkripce; helikasy RecQ; Animals; lidé; Humans; zvířata; replikace DNA; DNA; R-loops; DNA Replication; genomic instability